Farmers’ Behavioral Intention to Adopt Peer-To-Peer Lending Using UTAUT2 Approach - Hera Laxmi Devi Septiani; Ujang Sumarwan; Lilik Noor Yuliati; Kirbrandoko (Jurnal Manajemen & Agribisnis, 2020)
The limited access of smallholder farmers to funding sources is one of the main challenges facing Indonesia agriculture sector. In order to address this constraint some Fintech entities have initiated peer-to-peer (P2P) lending for funding the farming. Different from formal financial institution, farming funding P2P lending facilitates farmers by not requiring any collateral and applying profit sharing scheme instead of interest, which is in favor of smallholder farmers condition. Irrespective of the benefits, the adoption rate of farming funding P2P lending by farmers is still relatively low. Based on this background, the objective of this study is to investigate the factors influencing the behavioral intention of farmers to adopt farming funding P2P lending. This study uses variables of UTAUT2 and Schwartz Theory of Basic Values. The respondents of this research are 530 farmers in West Java, Indonesia who have and have not participated in farming funding P2P lending. The respondents are selected using purposive sampling method. The population of adopter farmers are the members of farming funding P2P lending providers Crowde and TaniFund. Whereas the non-adopter farmers are selected based on representation of various farming commodities. The data is analyzed using SEM, demonstrating the results that there are five variables showing significant correlation with behavioral intention to adopt P2P lending, which are performance expectancy, hedonic motivation, price value, habit and values. Keywords: consumer behavior, peer-to-peer lending, technology adoption, UTAUT2, valuess